Transfer Pricing in SMEs Critical Analysis and Practical Solutions - Solilova, Veronika (Contributions to Management Science,, 2018)
This book provides a detailed assessment of current approaches to transfer pricing in the context of small- and middle-sized enterprises (SMEs), including the newest update of Transfer Pricing Guidelines from 10 July 2017. It analyzes the transfer pricing rules for SMEs across the European Union (EU) and explores two alternative approaches as suitable solutions for current transfer pricing issues. The authors evaluate and discuss alternative approaches like Safe Harbour and Common Consolidated Corporate Tax Base (CCCTB). Taking into account the prominent role of SMEs in the European Union's economy, the book also puts forward policy recommendations to achieve the long-term goals of the EU's 2020 agenda.